Primary genetic disorders affecting high density lipoprotein (HDL) - Constantine E Kosmas; Delia Silverio; Andreas Sourlas; Frank Garcia; Peter D Montan; Eliscer Guzman (BioExcel Publishing Ltd, 2018)
There is extensive evidence demonstrating that there is a clear inverse correlation between plasma high density lipoprotein cholesterol (HDL-C) concentration and cardiovascular disease (CVD). On the other hand, there is also extensive evidence that HDL functionality plays a very important role in atheroprotection. Thus, genetic disorders altering certain enzymes, lipid transfer proteins, or specific receptors crucial for the metabolism and adequate function of HDL, may positively or negatively affect the HDL-C levels and/or HDL functionality and subsequently either provide protection or predispose to atherosclerotic disease. This review aims to describe certain genetic disorders associated with either low or high plasma HDL-C and discuss their clinical features, associated risk for cardiovascular events, and treatment options.